2022
DOI: 10.1101/2022.10.16.512414
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Legionellapara-effectors target chromatin and promote bacterial replication

Abstract: Legionella pneumophilareplicates intracellularly by secreting effectors via a type IV secretion system. One of these effectors is a eukaryotic methyltransferase (RomA) that methylates K14 of histone H3 (H3K14me3) to counteract host immune responses. However, it is not known howL. pneumophilainfection catalyses H3K14 methylation as this residue is usually acetylated. Here we show thatL. pneumophilasecretes a eukaryotic-like histone deacetylase (LphD) that specifically targets H3K14ac and works in synergy with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…With over 300 effectors, L. pneumophila has the largest described bacterial effector arsenal (Ensminger, 2016) and several examples of effector interplay that finetune effector function and the progression of pathogenesis (Kubori et al , 2010; Müller et al , 2010; Neunuebel et al , 2011; Tan et al , 2011; Tan & Luo, 2011; Mukherjee et al , 2011; Jeong et al , 2015; Urbanus et al , 2016; Shames et al , 2017; Valleau et al , 2018; Gan et al , 2019a; Wan et al , 2019; Gan et al , 2020; Schator et al , 2023). We previously performed the first genetic interaction screen of bacterial effectors, where we expressed every possible combination of L. pneumophila str.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With over 300 effectors, L. pneumophila has the largest described bacterial effector arsenal (Ensminger, 2016) and several examples of effector interplay that finetune effector function and the progression of pathogenesis (Kubori et al , 2010; Müller et al , 2010; Neunuebel et al , 2011; Tan et al , 2011; Tan & Luo, 2011; Mukherjee et al , 2011; Jeong et al , 2015; Urbanus et al , 2016; Shames et al , 2017; Valleau et al , 2018; Gan et al , 2019a; Wan et al , 2019; Gan et al , 2020; Schator et al , 2023). We previously performed the first genetic interaction screen of bacterial effectors, where we expressed every possible combination of L. pneumophila str.…”
Section: Discussionmentioning
confidence: 99%
“…Effectors in the latter class have the potential to regulate an action on the host in a spatial and/or temporal manner (Kubori & Galán, 2003). Cooperative effector interplay has also been identified such as the Legionella pneumophila paraeffectors LphD and RomA which work consecutively by first deacetylating and then methylating K14 of host histone 3 (Schator et al , 2023). Other effectors, such as LegC2, LegC3, and LegC7, directly cooperate–forming a SNARE-like complex with the human hVAMP4 protein to modulate membrane fusion (Shi et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, systematic screens [19,39] or individual studies of effector function [40][41][42][43][44][45][46][47][48] have identified some effectors that interfere with other effector activity rather than targeting a host cell protein. Regardless of the specific activities involved in these effector-effector interactions, two main models of interaction were revealed: indirect through counteracting modification of a shared host target, such as an effector pair recently described as para-effectors that target the host cell histone H3 [49], or direct through either complex formation or the modification of one effector by another. The direct interaction model led to the emerging concept of "metaeffector".…”
Section: Discussionmentioning
confidence: 99%
“…Recently, systematic screens 19,40 or individual studies of effector function [41][42][43][44][45][46][47][48][49] have identified some effectors that interfere with other effector activity rather than targeting a host cell protein. Regardless the specific activities involved in these effector-effector interactions, two main models of interaction were revealed: indirect through counteracting modification of a shared host target, such as an effector pair recently described as para-effectors that target the host cell histone H3 50 ; or direct through either complex formation or the modification of one effector by another. The direct interaction model led to the emerging concept of « metaeffector ».…”
Section: Discussionmentioning
confidence: 99%